Persistence of the Past Through the Objects from the Present - Hernández Romero, Yissel (Sociedad y Economía, 2012)
The journey of humankind through time is a movement whose evidence persists only in memory; this evidence wears away until disappearing, and it happens both individually and collectively. Considered as sensitive evidences, traces exceed the intangible and ephemeral conditions of mental images, revealing themselves in written, graphic and material forms. Socially valued, the past may be preserved, taken up again, and even re-interpreted. This article analyzes the expression of the past in material culture, the construction of meaning and its persistence in the present by means of old objects, revival and retro design.